2020
DOI: 10.1021/acsanm.0c01648
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-Phase TiO2 Nanotube–Nanorod Hybrid Arrays for Memory-Based Resistive Switching Devices

Abstract: Metal oxide nanostructure hybrid materials have garnered focused attention for next-generation memory-based devices. TiO 2 nanostructure hybrids dwell in that league of materials. In reference to that, the present work reports the growth of mixed-phase TiO 2 nanostructures (MxPh-TNs) and their hybrids by grafting metal nanoparticles (MNPs). MxPh-TNs are a concoction of rutile nanorods and anatase nanotubes, imaged using field-emission scanning electron microscope and further confirmed by micro-Raman spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…The curve of 2D‐2D MoS 2 /WS 2 heterostructures exhibits linear behaviour of the I–V curve, indicating the formation of Ohmic contact between 2D MoS 2 and 2D WS 2 . Similarly, the curve of 2D‐1D WS 2 /TiO 2 heterostructures exhibits non‐linear behaviour of the I–V curve, indicating the formation of Schottky contact between the 2D WS 2 and 1D TiO 2 [30] . Furthermore, IV curves confirm the conducting nature of WS 2 , 2D‐1D WS 2 /TiO 2, and 2D‐2D MoS 2 /WS 2 heterostructures.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…The curve of 2D‐2D MoS 2 /WS 2 heterostructures exhibits linear behaviour of the I–V curve, indicating the formation of Ohmic contact between 2D MoS 2 and 2D WS 2 . Similarly, the curve of 2D‐1D WS 2 /TiO 2 heterostructures exhibits non‐linear behaviour of the I–V curve, indicating the formation of Schottky contact between the 2D WS 2 and 1D TiO 2 [30] . Furthermore, IV curves confirm the conducting nature of WS 2 , 2D‐1D WS 2 /TiO 2, and 2D‐2D MoS 2 /WS 2 heterostructures.…”
Section: Resultsmentioning
confidence: 76%
“…Similarly, the curve of 2D-1D WS 2 /TiO 2 heterostructures exhibits non-linear behaviour of the I-V curve, indicating the formation of Schottky contact between the 2D WS 2 and 1D TiO 2 . [30] Furthermore, IV curves confirm the conducting nature of WS 2 , 2D-1D WS 2 /TiO 2, and 2D-2D MoS 2 /WS 2 heterostructures. A bias voltage was applied, with the Al layer serving as the upper electrode and the FTO layer serving as the lower electrode, which was grounded.…”
Section: Interfacial Investigationsmentioning
confidence: 69%
See 1 more Smart Citation
“…The presence of planes indicates that the obtained films belong to the 2D layered PEA 2 PbBr 4 , while the (002) plane represented by the star symbol corresponds to the TiO 2 . [ 35,36 ] It demonstrates the coexistence of 2D layered PEA 2 PbBr 4 and titanium oxide in the prepared switching films. Furthermore, all of PEA 2 PbBr 4 peaks belong to (00 n), indicating the layer‐by‐layer structure.…”
Section: Resultsmentioning
confidence: 93%
“…Among various one-dimensional nanostructures, different morphologies of titanium dioxide nanostructures have attracted much attention. To investigate the synergistic effect between TiO 2 anatase and rutile mixed-phase interfaces, Bamola et al reported mixed-phase TiO 2 nanostructures (MxPh-TNs) and their growth through mixtures of grafted metal nanoparticles (MNPs) [ 77 ]. Figure 11 a shows a schematic representation of the formation of this nanostructure.…”
Section: Optoelectrical Application Based On Tio 2 ...mentioning
confidence: 99%